Analisis Program OPOP Terhadap Kemandirian Ekonomi Pesantren di Pondok Pesantren Nurul Cholil Bangkalan - Novitasari; Alan Su'ud Ma'adi (Jurnal Ekonomi STIEP, 2024)
Every sector of society holds significant economic potential, including the world of Islamic boarding schools. In this case, there are various opportunities to increase economic potential. However, many pesantren still face challenges, especially in developing productive business units. One of the proposed solutions is the One Pesantren One Product (OPOP) Programme. This research uses a qualitative approach with data from interviews, observations, and documentation. The purpose of the study was to determine and analyse the role of OPOP in supporting the economic development and business independence of pesantren. The research findings show that the implementation of the OPOP programme at Pondok Pesantren Nurul Cholil plays an important role in encouraging economic development, especially the convection business. The pesantren successfully utilised the programme to improve professionalism, product quality, and expand market reach, supporting economic independence in a sustainable manner.